Influence of bolster-hanger length on the dynamic performance of high-speed EMS maglev vehicles. Issue 11 (2nd November 2022) - Feng, Yang; Zhao, Chunfa; Liang, Xin; Jiang, Zhongcheng
Abstract : To investigate the dynamic effects of bolster-hanger length on the 600 km/h high-speed EMS maglev vehicles, a dynamic model of three-car trainset is established, considering the kinematic relation of the bolster-hanger mechanism and the active levitation/guidance control system. Model validation is carried out by comparing simulated results with test results of Shanghai high-speed maglev vehicles. Then, the proposed model is used to simulate the dynamic response of maglev vehicles with four different hanger lengths of 0.12, 0.18, 0.24, 0.36 m and passing through the straight track, the horizontal curve and the vertical curve. Simulated results indicate that because of the too short hanger maglev vehicles cannot pass through safely the sharp horizontal curve, and deteriorate the lateral dynamic performance of maglev vehicles on the straight track. The too long hanger may increase the lateral displacement of the carbody and lateral forces of rubber stops of maglev vehicles on the large-radius horizontal curve. The hanger length has little influence on the dynamic response of maglev vehicle on the vertical curve. In sum, the medium-long (0.24 m) hanger can provide a stronger curve negotiation capacity and better ride quality of high-speed maglev vehicles.